2015
DOI: 10.1021/acs.organomet.5b00732
|View full text |Cite
|
Sign up to set email alerts
|

NHC Versus Pyridine: How “Teeth” Change the Redox Behavior of Iron(II) Complexes

Abstract: A series of octahedral iron(II) complexes with tetradentate NHC/pyridine hybrid ligands containing up to three pyridyl units was designed to study the influence of NHC and pyridine donors on the electronic structure of the metal center. Structural analysis of the iron complexes by NMR spectroscopy and single-crystal X-ray diffraction reveals different coordination modes of the ligand depending on the linkage of the different donor moieties. The oxidation potentials of all complexes correlate linearly with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…46 The 180 mV negative shift confirms that the bis-NHC ligand is a strong electron donor as compared to the bipyridine ligand. 47 The redox potential of 1 is therefore very close to the redox potential of ABTS (E = +0.50 V vs Ag/AgCl at pH 7), the mainly used redox mediator for oxygen reduction by multicopper oxidases. 48 Thus, complex 1 has a well-suited redox potential for mediating the high potential oxygen reduction by these enzymes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…46 The 180 mV negative shift confirms that the bis-NHC ligand is a strong electron donor as compared to the bipyridine ligand. 47 The redox potential of 1 is therefore very close to the redox potential of ABTS (E = +0.50 V vs Ag/AgCl at pH 7), the mainly used redox mediator for oxygen reduction by multicopper oxidases. 48 Thus, complex 1 has a well-suited redox potential for mediating the high potential oxygen reduction by these enzymes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13) led to an excited 3 MLCT state lifetime of 13 ps. 266 Another highly relevant publication around this time came from Kuhn and coworkers 267 who demonstrated that the electronic structure of NHC iron(II) complexes is strongly influenced by the number of NHC donors. Cyclic voltammetric data confirmed a linear correlation between the oxidation potentials of the iron(II) complexes and the number of NHC donors.…”
Section: N-heterocyclic Carbene Era Arrivesmentioning
confidence: 99%
“…These ligands consist of two rigid pyridyl-NHC moieties that are linked by a flexible propylene or o -xylylene spacer. Related tetradentate ligands containing varying numbers of NHC versus pyridyl moieties have been reported and were found to influence the redox behavior of iron­(II) complexes . In our case, the inclusion of two opposing elements, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Related tetradentate ligands containing varying numbers of NHC versus pyridyl moieties have been reported and were found to influence the redox behavior of iron(II) complexes. 14 In our case, the inclusion of two opposing elements, i.e. coplanar C/N vs perpendicular diNHC chelation (Chart 1), should prevent simple in-plane coordination of the potentially tetradentate ligand, while the bromide counteranions are a source for competing coligands.…”
Section: ■ Introductionmentioning
confidence: 85%